2021
DOI: 10.3390/ijms22136854
|View full text |Cite
|
Sign up to set email alerts
|

GMI, an Immunomodulatory Peptide from Ganoderma microsporum, Restrains Periprosthetic Joint Infections via Modulating the Functions of Myeloid-Derived Suppressor Cells and Effector T Cells

Abstract: Periprosthetic joint infections (PJIs) caused by Staphylococcus aureus infection are difficult to treat due to antibiotic resistance. It is known that the biofilms from methicillin-resistant S. aureus (MRSA) promote expansion of myeloid-derived suppressor cells (MDSCs) to suppress T-cell proliferation and benefit bacterial infections. This study finds that GMI, a fungal immunomodulatory peptide isolated from Ganoderma microsporum, suppresses MDSC expansion to promote the proliferation of cytotoxic T cells. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…The relationship between GMI and human body immunity is also noteworthy as it has been mentioned in various articles. GMI could restrict MDSC expansion to induce the proliferation of cytotoxic T cells [64] . In addition, GMI has been shown to have similar protein sequence and structure in comparison with Lingzhi 8 (LZ8) from Ganoderma microsporum.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between GMI and human body immunity is also noteworthy as it has been mentioned in various articles. GMI could restrict MDSC expansion to induce the proliferation of cytotoxic T cells [64] . In addition, GMI has been shown to have similar protein sequence and structure in comparison with Lingzhi 8 (LZ8) from Ganoderma microsporum.…”
Section: Discussionmentioning
confidence: 99%
“…A 2.0 Å structure of GMI was solved and GMI showed a dimer:dimer quaternary structure with non-covalent interactions through the N-terminal helices (PDB ID 3KCW, [16] ). Furthermore, GMI with the same quality were evaluated in the platform for the anti-tumor activity and immunomodulation under immune disorder/disease model, and GMI showed a variety of bioactivities in the application for oncology [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [44] , [43] , immuno-oncology [53] , [54] , [55] , [56] , [57] , and immunology [59] , [60] , [62] , [63] , [64] , [61] , [58] , [65] . Although these promising findings are attractive for the further clinical application, the quality and the safety are always the major concerns.…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study, the polysaccharides from G. lucidum showed no cytotoxic effect on CML and HeLa cells [64]. Peng et al investigated the effect of one immunomodulatory peptide from G. microsporum on S. aureus methicyllin-resistant Staphylococcus aureus (MRSA) promoted expansion of myeloid-derived suppressor cells (MDSCs) to suppress T-cell proliferation and the peptide increased IL-6 and TNF-alpha levels and thus the author suggested that G. microsporum could be useful for periprosthetic joint infections induced by S. aureus [65]. Selected biological activities of terpenes from Ganoderma spp.…”
Section: Anticancer and Cytotoxicity Effectsmentioning
confidence: 99%